2019
DOI: 10.1155/2019/8562384
|View full text |Cite
|
Sign up to set email alerts
|

Production of Coconut Aroma in Solid-State Cultivation: Screening and Identification ofTrichodermaStrains for 6-Pentyl-Alpha-Pyrone and Conidia Production

Abstract: The polyketide, 6-pentyl-alpha-pyrone (6-PP), has a characteristic coconut aroma and is produced by manyTrichodermaspecies. In this study, we screened formerly isolatedTrichodermastrains for 6-PP production grown using solid-state fermentation (SSF). Sugarcane bagasse supplemented with a nutrient solution was used as the support material for the culture. We detected outstandingly strong 6-PP production in the case of twoTrichodermastrains in this experiment. The strains were identified based on internal transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 25 publications
(14 citation statements)
references
References 30 publications
1
10
0
3
Order By: Relevance
“…Lastly, an increase in inoculum size from 5% led to a progressive increase in conidia production, reaching the highest value at 10% for T. longibrachiatum AU158. The effect of inoculum size on conidia production was also studied by Hamrouni et al [ 86 ], who reported that maximum conidia production was obtained using a 5% inoculum. A smaller inoculum may not be adequate for growth initiation and may delay the lag phase as well as enzyme synthesis [ 35 ], whereas a high inoculum size shortens the lag phase but may also increase competition for limiting nutrients due to overcrowded growth of the organism per unit substrate [ 87 ].…”
Section: Discussionmentioning
confidence: 97%
“…Lastly, an increase in inoculum size from 5% led to a progressive increase in conidia production, reaching the highest value at 10% for T. longibrachiatum AU158. The effect of inoculum size on conidia production was also studied by Hamrouni et al [ 86 ], who reported that maximum conidia production was obtained using a 5% inoculum. A smaller inoculum may not be adequate for growth initiation and may delay the lag phase as well as enzyme synthesis [ 35 ], whereas a high inoculum size shortens the lag phase but may also increase competition for limiting nutrients due to overcrowded growth of the organism per unit substrate [ 87 ].…”
Section: Discussionmentioning
confidence: 97%
“…Solid-state fermentation (SSF), an environmentally friendly technique, which uses solid substrates at low moisture levels, requires suitable solid substrate among agroindustrial materials [20]. Various raw materials are used for SSF, for example, winery and brewery waste, olive mill waste, sunflower cake, sugarcane bagasse, fruit's peels and pulps, cereal brans, and BW [21][22][23][24][25]. In this process, microorganisms grow and produce a wide variety of products such as mushrooms [26], aroma [21,27], microbial oil [28,29], preservatives like fumaric acid [30,31], enzymatic production of wax esters [32], and enzymes [14,27], thus reducing the cost of production, as reported by these studies.…”
Section: Introductionmentioning
confidence: 99%
“…As well as for all microorganisms, Trichoderma SMs play pivotal roles in chemical defense and communication, and some of them are largely studied, showing antibiotic abilities to be of importance in biocontrol applications (peptaibols, polyketides, pyrones, terpenes and diketopiperazine-like compounds) [72]. Among these compounds, 6-penthyl-α-pyrone (6-PP) is the most studied for its antifungal property and is responsible for the "coconut aroma" associated with some species of Trichoderma, such as T. harzianum, T. virens, T. asperellum [59,[73][74][75][76], and that in our study was observed in all the tested T. hamatum isolates, and weakly in T. asperellum SG4. In this study, the capability of Trichoderma to act through antibiosis strategy was assessed by also evaluating the eventual release of diffusible and volatile secondary metabolites, as well as their inhibitory activity towards the growth of P. xcambivora in vitro.…”
Section: Discussionmentioning
confidence: 99%